Resisting Corporate Corruption, 3rd Edition - Arbogast, Stephen (Wiley-Scrivener, 2017)
Resisting Corporate Corruption teaches business ethics in a manner very different from the philosophical and legal frameworks that dominate graduate schools. The book offers twenty-eight case studies and nine essays that cover a full range of business practice, controls and ethics issues. The essays discuss the nature of sound financial controls, root causes of the Financial Crisis, and the evolving nature of whistleblower protections. The cases are framed to instruct students in early identification of ethics problems and how to work such issues within corporate organizations. They also provide would-be whistleblowers with instruction on the challenges they'd face, plus information on the legal protections, and outside supports available should they embark on that course. Some of the cases illustrate how 'The Young are the Most Vulnerable, ' i.e. short service employees are most at risk of being sacrificed by an unethical firm. Other cases show the ethical dilemmas facing well-known CEOs and the alternatives they can employ to better combine ethical conduct and sound business strategy. Through these case studies, students should emerge with a practical toolkit that better enables them to follow their moral compass. Finally, the cases provide an in depth look at how a corporation becomes progressively corrupted (Enron), how the Financial Crisis was rooted in ethical decay at institutions as diverse as Countrywide, Goldman Sacks, Citigroup, Fannie Mae and Moody's, and at the ethical challenges that persist in the post-Crisis, post-Dodd-Frank environment.